Effects of hydrogen relative humidity on the performance of an air-breathing PEM fuel cell: A numerical study. Issue 4 (1st July 2019) - Chen, Zhenxiao; Ingham, Derek; Ismail, Mohammed; Ma, Lin; Hughes, Kevin J.; Pourkashanian, Mohamed
Abstract : Purpose: The purpose of this paper is to investigate the effects of hydrogen humidity on the performance of air-breathing proton exchange membrane (PEM) fuel cells. Design/methodology/approach: An efficient mathematical model for air-breathing PEM fuel cells has been built in MATLAB. The sensitivity of the fuel cell performance to the heat transfer coefficient is investigated first. The effect of hydrogen humidity is also studied. In addition, under different hydrogen humidities, the most appropriate thickness of the gas diffusion layer (GDL) is investigated. Findings: The heat transfer coefficient dictates the performance limiting mode of the air-breathing PEM fuel cell, the modelled air-breathing fuel cell is limited by the dry-out of the membrane at high current densities. The performance of the fuel cell is mainly influenced by the hydrogen humidity. Besides, an optimal cathode GDL and relatively thinner anode GDL are favoured to achieve a good performance of the fuel cell. Practical implications: The current study improves the understanding of the effect of the hydrogen humidity in air-breathing fuel cells and this new model can be used to investigate different component properties in real designs. Originality/value: The hydrogen relative humidity and the GDL thickness can be controlled to improve the performance of air-breathing fuel cells.